Issues of Increasing the Efficiency of Small Business in Rural Areas (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The article discusses the issues of improving the efficiency of small business in the village, which occupy an important place in the development of the economy, ensuring employment of the population through the creation of new jobs, as well as issues related to factors that serve to improve the well-being of people.